PENGARUH PENAMBAHAN KHITOSAN TERHADAP BEBERAPA KARATERISTIK FILM RAMAH LINGKUNGAN (FRL) BERBASIS PATI SAGU (Metroxylon sp.) - CAHAYA OKTAVIA OKTAVIA '; RASWEN EFENDI EFENDI '; VONNY SETIARIES JOHAN SETIARIES JOHAN (Jurnal Sagu, 2015)
ABSTRACTBiodegradable film is plastic which can be decompose naturally by microorganism to be sustainablecompounds. The main raw material is from sago starch. But biodegradable film based on starch give lesscharateristic. The purpose of research to getting the best combination of chitosan on making biodragadablefilm based by sago starch. The research using completely randomized design (CRD). The Results analysis ofvariance showed a significantly (P<0,05) and followed by duncan’s new multiple range test level of 5 %.Chitosan concentration used in this study was 2% , 3% , 4% , 5% and 6%. The best combination is a thirdtreatment that chitosan concentration of 4% with a water content of 18,72 %, a thickness of 0,04 mm, waterresistance of 25,95 % and degradation of 81,31 %.Key words : Biodegradable film, sago starch, chitosan.